Pharmacists’ Perceptions of 3D Printing and Bioprinting as Part of Personalized Pharmacy: A Cross-Sectional Pilot Study in Bulgaria - Anna Mihaylova; Antoniya Yaneva; Dobromira Shopova; Petya Kasnakova; Stanislava Harizanova; Nikoleta Parahuleva; Rumyana Etova; Ekaterina Raykova; Mariya Semerdzhieva; Desislava Bakova (Pharmacy)
Advances in pharmaceutical technology have positioned 3D printing and bioprinting as promising tools for developing personalized drug therapies. These innovations may redefine compounding practices by enabling precise, patient-specific drug formulations. Evaluating pharmacists’ readiness to adopt such technologies is therefore becoming increasingly important. Aim: The aim of this study is to investigate pharmacists’ knowledge, attitudes, and perceived barriers regarding the application of 3D printing and bioprinting technologies, as well as their perspectives on the regulation and implementation of these technologies in the context of personalized pharmacy. Materials and Methods: A custom-designed questionnaire was developed for the purposes of this pilot study, based on a review of the existing literature and informed by expert consultation to ensure conceptual relevance and clarity. The survey was conducted between September and December 2024. The data collection instrument comprises three main sections: (1) sociodemographic and professional characteristics, (2) knowledge regarding the applications of 3D printing and bioprinting in pharmacy, and (3) attitudes toward the regulatory framework and implementation of these technologies. Results: A total of 353 respondents participated, and 65.5% of them (n = 231) correctly distinguished between the concepts of “3D printing” and “bioprinting.” More than 25% (n = 88) were uncertain, and 8.5% (n = 30) were unable to differentiate between the two. Regarding the perceived benefits of personalized pharmacy, 83% (n = 293) of participants identified “the creation of personalized medications tailored to individual needs” as the main advantage, while 66% (n = 233) highlighted the “optimization of drug concentration to enhance therapeutic efficacy and minimize toxicity and adverse effects.” Approximately 60% (n = 210) of the pharmacists surveyed believed that the introduction of 3D-bioprinted pharmaceuticals would have a positive impact on the on-site preparation of customized drug formulations in community and hospital pharmacies. Lack of regulatory guidance and unresolved ethical concerns were identified as primary barriers. Notably, over 40% (n = 142) of respondents expressed concern that patients could be subjected to treatment approaches resembling “laboratory experimentation.” Nearly 90% (n = 317) of participants recognized the need for specialized training and expressed a willingness to engage in such educational initiatives. Conclusions: Three-dimensional printing and bioprinting technologies are considered cutting-edge instruments that may contribute to the advancement of pharmaceutical practice and industry, particularly in the field of personalized medicine. However, respondents’ views suggest that successful integration may require improved pharmacist awareness and targeted educational initiatives, along with the development and adaptation of appropriate regulatory frameworks to accommodate these novel technologies in drug design and compounding.